Understanding Buddhayāna and Kalyānamitta (good friend) in the religious character of Buddhist Youth in North Lombok - Pebri Resky Adita; Hendri Ardianto; Susanto Susanto (International Journal of Science and Applied Science: Conference Series, 2025)
The formation of religious character in the younger generation is greatly influenced by a deep understanding of Buddhayāna teachings and the presence of Kalyānamitta. Buddhayāna teachings provide a spiritual foundation, while Kalyānamitta provides important social and spiritual support. This study focuses on the belief that the interaction between the two has a major impact on the religious character of young people. This study explores the influence of understanding Buddhayāna and Kalyānamitta (good friends) on the religious character of Buddhist youth. Religious character is an important aspect in increasing tolerance among fellow human beings. The formation of religious character in the younger generation is greatly influenced by a deep understanding of buddhayāna teachings and the existence of kalyānamitta. Buddhāyāna teachings provide a foundation of spiritual values, while kalyānamitta provides important social and spiritual support. This study focuses on the belief that the interaction between the two has a significant impact on the religious character of the younger generation. This study uses a quantitative descriptive method. This study uses a quantitative descriptive method. The number of samples in this study was 60 respondents. The sample was determined using the Proportional Random Sampling technique. The research instrument consisted of a questionnaire that measured the level of understanding of Buddhayāna, Kalyānamitta, and Religious Character. The data collection techniques were questionnaires, interviews, and documentation. The data were collected through questionnaires that were tested for validity and reliability, then analyzed using multiple regression techniques to test the influence of understanding of buddhayāna and kalyānamitta (good friends) on religious character. In proving and analyzing this, validity and reliability tests, classical assumption tests, multiple linear regression tests, and f (simultaneous) and t (partial) tests were used. The results of the study show that understanding of buddhayāna and kalyānamitta has a positive and significant effect on the religious character of the younger generation.